Wahyu dan Rasionalitas sebagai Dasar Moralitas: Studi Komparatif Pemikiran Muhammad Taqî Misbâh al-Yazdî dan Franz Magnis-Suseno - Andrio Putra Tahiro; Fardiana Fikria Qur'any (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2025)
The relationship between religion and morality remains one of the central debates in contemporary moral philosophy. While some philosophers regard divine revelation as the ultimate foundation of moral values, others argue that morality is grounded primarily in human reason and autonomy. This article offers a comparative analysis of the moral philosophies of Muhammad Taqî Misbâh al-Yazdî and Franz Magnis-Suseno, focusing on the relationship between revelation and reason as the foundation of religious morality. Employing qualitative library research with a comparative philosophical approach, the study examines the principal works of both thinkers. The findings reveal that Misbâh al-Yazdî considers revelation to be the supreme normative source that legitimizes and directs moral conduct, whereas Magnis-Suseno emphasizes reason, freedom, and conscience as the primary basis of morality while acknowledging the ethical significance of religion. Despite their different epistemological orientations, both thinkers converge in viewing morality as a means of cultivating universal goodness, respect for human dignity, and social responsibility. This study argues that revelation and reason should not be understood as competing sources of morality but as complementary foundations for developing ethical life in a pluralistic society.